The protective performance of rubber pads for penetration fuze - Ding, Libo; Zhang, An; Peng, Junwei; Li, Changsheng (Frontiers in Materials, 2023)
To ensure the reliable functioning of hard target-penetrating fuses on the battlefield, this study focuses on research related to fuse protective pads. The main factors causing fuse functional failure are summarized, and a simplified model of projectile penetration into target plates is established. The design conditions for the yield stress parameter of the fuse casing material are derived based on stress wave propagation theory. Modal analysis of the projectile is conducted using dynamic simulation software ANSYS to determine its vibration modes and low-pass filtering frequency. Static compression experiments are performed on different rubber materials (nitrile rubber, fluorine rubber, silicone rubber, and natural rubber) to obtain stress-strain curves and constitutive model parameters.Marshall hammer tests were carried out on rubber pads of different materials and thicknesses, confirming the validity of the simulation results and the feasibility of rubber filtering. The study indicates that when using a 2 mm thick rubber pad for protection, natural rubber provides the best protection. With a 4 mm thick rubber pad, nitrile rubber offers the best protection. When using a 6 mm thick rubber pad, nitrile rubber shows the best protective performance. Under a 13-tooth tooling impact load, the best protection is achieved using a 2 mm thick natural rubber pad. When using a 6 mm thick pad, silicone rubber provides the best protection. Under a 15-tooth tooling impact load, fluorine rubber provides the best protection when using a 2 mm thick pad, while silicone rubber offers the best protection when using a 6 mm thick pad. Under a 17-tooth tooling impact load, natural rubber offers the best protection when using a 2 mm thick pad, and fluorine rubber demonstrates the best protection when using a 6 mm thick pad. The obtained research results provide a reference for protective methods of hard target-penetrating fuses.